2008
DOI: 10.1901/jaba.2008.41-527
|View full text |Cite
|
Sign up to set email alerts
|

Voucher‐based Contingent Reinforcement of Smoking Abstinence Among Methadone‐maintained Patients: A Pilot Study

Abstract: This study evaluated the efficacy of a contingency management (CM) intervention to promote smoking cessation in methadone-maintained patients. Twenty participants, randomized into contingent (n 5 10) or noncontingent (n 5 10) experimental conditions, completed the 14-day study. Abstinence was determined using breath carbon monoxide and urine cotinine levels. Contingent participants received voucher-based incentives for biochemical evidence of smoking abstinence. Noncontingent participants earned vouchers indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
60
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 47 publications
9
60
1
Order By: Relevance
“…The experimental condition with significantly greater during-treatment abstinence also achieved significantly greater post-treatment abstinence during an 18-month follow-up period. We know of two published reports with cigarette smokers where abstinencecontingent monetary payment was used to create significantly different levels of abstinence while the contingencies were in place and then assessed abstinence during followup (Dunn et al 2008;Gilbert et al 1999). In both instances abstinence levels post-treatment were several-fold higher in the condition with greater during-treatment abstinence compared to the condition with less, but in both studies the differences failed to achieve statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental condition with significantly greater during-treatment abstinence also achieved significantly greater post-treatment abstinence during an 18-month follow-up period. We know of two published reports with cigarette smokers where abstinencecontingent monetary payment was used to create significantly different levels of abstinence while the contingencies were in place and then assessed abstinence during followup (Dunn et al 2008;Gilbert et al 1999). In both instances abstinence levels post-treatment were several-fold higher in the condition with greater during-treatment abstinence compared to the condition with less, but in both studies the differences failed to achieve statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The longer half-life of cotinine (~16-20 h; Ahijevych et al 2002;Benowitz et al 2002;Skarping et al 1988) relative to CO provides greater assurance against low-level smoking between visits. Additionally, our group has previously demonstrated that a similar procedure is effective in promoting smoking abstinence among pregnant women ) and methadone maintained outpatients (Dunn et al 2008).…”
mentioning
confidence: 95%
“…Of course, the precipitous change in CO levels between Days 13 and 14 corresponding to the change from noncontingent to abstinence-contingent reinforcement in the 1C condition further illustrated the effectiveness of the reinforcement contingencies to bring smoking under experimental control. The purpose for exerting such control in the present study was strictly scientific, but the abstinence-contingent reinforcement methods that have been developed as part of this research effort have been successfully extended to important clinical applications, including, for example, the promotion of smoking cessation among pregnant women and opioid-dependent patients (Dunn, Sigmon, Thomas, Heil, & Higgins, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Research on CM for treating smoking in SUD patients has focused primarily on opioid maintenance settings, in part because clinic attendance is daily, coinciding with the ability to assess smoking with CO tests and reinforce abstinence (Dunn et al, 2010;Dunn, Sigmon, Thomas, Heil, & Higgins, 2008;Shoptaw et al, 2002;Shoptaw, Jarvik, Ling & Rawson, 1996). Two demonstration projects examined CM for smoking abstinence in nonopioid medication settings.…”
Section: Introductionmentioning
confidence: 99%